'Thermo-mechanical behavior of alternative material combinations for full-arch implant-supported hybrid prostheses with short cantilevers'. (May 2023) - Haroyan-Darbinyan, Evelina; Romeo-Rubio, Marta; Río-Highsmith, Jaime Del; Lynch, Christopher D.; Castillo-Oyagüe, Raquel
Abstract: Objectives: To compare the fracture resistance (FR) of three combinations of materials for full-arch maxillary implant-supported hybrid prostheses (HPs) with short cantilevers (≤ 10 mm). Methods: Maxillary HPs were fabricated and classified as follows ( n  = 5 each): Group-1 (CC-A, control ): acrylic-resin-veneered Co-Cr frameworks; Group-2 (CF-A): acrylic-resin-veneered carbon-fiber mesostructures; and Group-3 (CF-R): composite-resin-veneered carbon-fiber frames. Specimens were thermal-cycled (5, 000 cycles; 5 °C–55 °C; dwell time: 30 s). Vertical loads were applied until failure, first at the 10-mm-long cantilever (LC), and, afterwards, at the anterior region (AR), using a universal testing machine (crosshead speed: 0.05 mm/s). The fracture pattern was assessed by stereomicroscope and SEM. The one-way ANOVA, the Bonferroni, and the independent samples t tests, were run ( α = 0.05). Results: At LC, CF-A, and CC-A samples exhibited the highest FR values ( p < 0.001), showing no differences to each other. At AR, CC-A specimens recorded the highest FR, followed by CF-A samples ( p < 0.001). CF-R HPs displayed the lowest FR at both locations ( p < 0.001). The only group with differences between the tested sites was the CC-A, the AR being more resistant ( p < 0.001). Most CC-A and CF-A HPs failed cohesively. CF-R prostheses mainly failed adhesively. Conclusions: Maxillary HPs with short cantilevers (≤ 10 mm) made of Co-Cr or carbon-fiber veneered with acrylic resin demonstrated an adequate mechanical resistance (> 900 N). Clinical significance: For maxillary HPs with cantilevers up to 10 mm, acrylic-veneered carbon- fiber mesostructures may be recommended, whereas coating carbon-fiber frames with composite resin seems not suitable.